Polysome analysis and RNA purification from sucrose gradients - Mašek, Tomáš; Valášek, Leoš; Pospíšek, Martin (Methods in molecular biology (Clifton, N.J.), 2011)
Velocity separation of translation complexes in linear sucrose gradients is the ultimate method for both analysis of the overall fitness of protein synthesis as well as for detailed investigation of physiological roles played by individual factors of the translational machinery. Polysome profile analysis is a frequently performed task in translational control research that not only enables direct monitoring of the efficiency of translation but can easily be extended with a wide range of downstream applications such as Northern and Western blotting, genome-wide microarray analysis or qRT-PCR. This chapter provides a basic overview of the polysome profile analysis technique and the RNA isolation procedure from sucrose gradients. We also discuss possible experimental pitfalls of data normalization, describe main alternatives of the basic protocol and outline a novel application of denaturing RNA electrophoresis in several steps of polysome profile analysis.
Keywords: elektroforéza; Centrifugation, Density Gradient; centrifugace - gradient hustoty; regulace genové exprese; polyribozomy; Data Interpretation, Statistical; Gene Expression Regulation; Polyribosomes; proteosyntéza; Yeasts; kvasinky; interpretace statistických dat; RNA; Electrophoresis; Protein Biosynthesis